Growing Up under Corporate Capitalism: The Problem of Marketing to Children, with Suggestions for Policy Solutions. Issue 1 (5th January 2016) - Kasser, Tim; Linn, Susan
Abstract : Bronfenbrenner's ecological model of development suggests that children are affected by the economic system under which they live. Corporate capitalism is one such economic system, and evidence suggests that the focus on profit and power characteristic of deregulated, competitive forms of capitalism can suppress how much citizens prioritize the values that support the nurturing of children. One manifestation of this capitalist ideology is the practice of marketing to children, a practice known to be associated with a variety of negative outcomes for children. We present empirical evidence supporting these claims and conclude by proposing numerous policies aimed at reducing children's exposure to marketing. The policies, many of which have widespread public support, can be implemented in a number of types of institutions that directly or indirectly affect children, including professional organizations, schools, businesses, and all levels of government.